STRENGTHENING RELIGIOUS MODERATION IN ISLAMIC EDUCATION CURRICULUM: IN HIGH SCHOOL SYSTEMATIC LITERATURE REVIEW AND QUALITATIVE INSIGHTS - Fazri, Ayum; Sari, Ika Mutia; Triana, Rini; Dari, Wulan; Rinaldi, Rizky (Yayasan Amanah Nur Aman, 2025)
This study analyzes strategies for strengthening religious moderation in the Islamic Religious Education (PAI) curriculum in Senior High Schools through a Systematic Literature Review (SLR) with a qualitative thematic approach, identifying three main implementation strategies: integration of wasathiyah values in PAI curriculum development based on Minister of Religious Affairs Decree Number 183 of 2019 with emphasis on strengthening students' social attitude competencies, optimization of PAI teachers' roles as models through implementation of student-centered learning methods and utilization of educational technology, and strengthening students' religious literacy and critical thinking skills as strategies for addressing digital extremism, where the research concludes that such implementation plays a crucial role in shaping students who are religious, tolerant, character-driven, and able to adapt to global challenges through holistic synergy between curriculum policies, teacher capacity, and educational environment support.